2022
DOI: 10.1002/mds.29214
|View full text |Cite
|
Sign up to set email alerts
|

Corticospinal Suppression Underlying Intact Movement Preparation Fades in Parkinson's Disease

Abstract: Background In Parkinson's disease (PD), neurophysiological abnormalities within the primary motor cortex (M1) have been shown to contribute to bradykinesia, but exact modalities are still uncertain. We propose that such motor slowness could involve alterations in mechanisms underlying movement preparation, especially the suppression of corticospinal excitability—called “preparatory suppression”—which is considered to propel movement execution by increasing motor neural gain in healthy individuals. Methods On t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 92 publications
(187 reference statements)
0
15
2
Order By: Relevance
“…In conditions like Parkinson’s disease (PD), which is associated with cognitive dysfunction and can affect patients early on (Dirnberger & Jahanshahi, 2013), there is some evidence supporting this idea. More relevant to our conceptual model, recent work by Wilhelm et al (2022) found that PD patients display reduced CS suppression during movement preparation in comparison to healthy control individuals. Relatedly, alcohol dependent individuals and binge drinkers, who commonly show abnormalities in prefrontal networks, show a similar impairment of CS suppression during action preparation (Grandjean & Duque, 2020; Quoilin et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…In conditions like Parkinson’s disease (PD), which is associated with cognitive dysfunction and can affect patients early on (Dirnberger & Jahanshahi, 2013), there is some evidence supporting this idea. More relevant to our conceptual model, recent work by Wilhelm et al (2022) found that PD patients display reduced CS suppression during movement preparation in comparison to healthy control individuals. Relatedly, alcohol dependent individuals and binge drinkers, who commonly show abnormalities in prefrontal networks, show a similar impairment of CS suppression during action preparation (Grandjean & Duque, 2020; Quoilin et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Rapid eye movements, a phasic REM sleep activity, have been associated with the activation of the motor cortex during sleep [32]. One possible explanation for the reduced REM density in PD may be reduced cortical activation during REM sleep, which parallels the reduced cortical activation observed during wakefulness in individuals with bradykinesia [14,33,34]. The similarity between the two phenomena and the negative correlation between REM density and the bradykinesia score suggests a potential common underlying mechanism.…”
Section: Discussionmentioning
confidence: 98%
“…That is, MEPs were reduced relative to resting conditions, indicating a strong suppression of corticospinal excitability in the patient, consistently reported in healthy subjects ( 47 , 72 , 79 , 86 ). As mentioned earlier, this neural suppression of motor excitability during action preparation has been related to some sort of inhibitory control allowing to avoid premature responding during action preparation ( 42 , 43 , 58 ), even if there are also alternative views though not necessarily incompatible [( 48 , 51 ) for an alternative view]. Our interpretation of rather good inhibitory control in the patient (based on the observation of normal preparatory suppression) is in line with growing evidence indicating normal inhibitory functions in GTS.…”
Section: Discussionmentioning
confidence: 99%
“…When probed before the imperative, MEPs elicited in taskrelevant and task-irrelevant muscles of both hands are strongly suppressed relative to resting conditions (42,(45)(46)(47). This drastic suppression of motor excitability is thought to help inhibit premature or inappropriate responses and, more generally, to ensure some sort of inhibitory control during action preparation [ (42,43); but see also (48)(49)(50)(51) for an alternative hypothesis]. This idea comes from the observation that motor suppression is deeper when movement preparation entails overcoming sensory conflict (52,53).…”
Section: Introductionmentioning
confidence: 99%